An exploration into psychological attributes and mental techniques utilized in professional esports - Planting, Zacharias; Salomaa, Hermanni (2024)
The purpose of this thesis was to explore the most important psychological attributes in esports and the types of mental techniques utilized by professionals and coaches. The research data was collected in spring 2023 through interviews. We interviewed four (4) players and two (2) coaches, all professionals in the field of esports. The interviews followed a semistructured interview method. Five interviews were conducted remotely via video call using Zoom, and one was conducted at the premises of the University of Jyväskylä. The duration of the interviews ranged between 60 minutes and 91 minutes. We chose qualitative data-driven content analysis as our method of analysis, and the philosophical foundation of our research was phenomenological-hermeneutic. The thesis delved into the essential psychological attributes and mental techniques in esports, as identified by professionals in the field. The collected data comprised 99 pages of transcribed interviews, formatted in 12-point font with 1.5 line spacing between paragraphs. Our findings, totaling 607 mentions, highlights the significance of team dynamics (n=154), psychological attributes (n=277), and mental techniques (n=176). These were organized into 30 upper classes and 3 main categories, illustrating the intricate interplay of performance psychology within professional esports. This thesis investigated the psychological attributes and mental techniques essential for professional esports performance, categorizing them into three main classes: team dynamics, psychological attributes, and mental techniques. It highlights the importance of attributes such as awareness, confidence, and focus, along with techniques like self-regulation and imagery, for peak performance. Team dynamics, including cohesion and communication, were also identified as crucial for success. The study provides valuable insights into esports psychology and the potential implementation of mental training practices. It also highlights 'flow-state' as a promising area for future investigation, informed by the results obtained. By illustrating the interconnectedness of these elements, the thesis advocates for a holistic approach to enhancing esports performance, suggesting landscapes for further exploration in the interplay between psychological attributes, mental techniques, and team dynamics.